EFL STUDENTS’ PERCEPTIONS TOWARD EDUCATIONAL VIDEO PROJECTS - Sukandi, Muhammad; Hasbi, Muhamad (JETA (Journal of English Teaching and Applied Linguistic), 2024)
This research aimed to know the EFL students’ perceptions toward educational video projects in Computer Assisted Language Learning (CALL) class. This research method was descriptive qualitative, with the research instrument used being interviews with 7 students who had completed educational video project assignments in the CALL class of the English Education Department at UIN Salatiga. The result of the study revealed that most students showcased positive perceptions of the educational video project, proven by some of their testimonial words such as interesting, exciting, relevant to the study, and beneficial. The project helped them to develop their digital skills, especially in video editing, improve their speaking skills, mainly their pronunciation, increase their confidence in speaking, develop their creativity in making an educational video, and learn teamwork. They also encountered a few obstacles during the completion of the project, especially those related to the recording and video editing process, their lack of confidence in speaking in front of the camera, and difficulty finding a suitable location and time for recording.